Model Emotional Experience and Memorable Tourism Experience in Formation Word Of Mouth in Forest Tourism Mangrove Cilamaya - Widia Maelanicha; Citra Savitri; Syifa Pramudita Faddila (International Journal of Economics and Management Research, 2025)
This research aims to analyze the influence of emotional experience and memorable tourism experience on word of mouth in Cilamaya Mangrove Forest Tourism. These three variables are important in promoting tourist destinations. Emotional refers to the response of tourists' feelings during the visit, memorable is related to an imprinted experience, while word of mouth is communication from word of mouth when tourists share their experiences with others.The study used a quantitative descriptive verification approach with purposive sampling method and the number of respondents was 150 people. Data processing is done using Structural Equation Modeling based on Partial Least Square. The results showed that emotional variables had an insignificant effect on word of mouth. This indicates that the emotional aspect alone is not strong enough to encourage tourists to share their experiences. In contrast, memorable experiences are proven to have a significant influence on word of mouth. This means that the deeper the impression left by the destination, the more likely tourists are to share it with others. The implication of this finding is that it is important for destination managers to create memorable experiences through improved facilities, educational activities, and good service to strengthen promotion from tourists to tourists on an ongoing basis.Keywords: E, ,